Pengaruh Locus of Control, Love of Money, dan Kecerdasan Emosional Terhadap Persepsi Etis Mahasiswa Mengenai Profesi Akuntan (Studi pada Mahasiswa Akuntansi FEB UNTAG Semarang) - Aditya Ramadhaniar El Islamy; Janti Soegiastuti (Jurnal Ilmiah Ekonomi, Akuntansi, dan Pajak, 2024)
Locus of control is an individual's perception of who determines his fate, which perception greatly influences the auditor, Locus of control leads to individuals influencing good and bad events in their lives, Accountants are individuals who pursue work in the field of accounting and accountants will be in the spotlight for the public if there is fraud or violations related to finance. An accountant must have ethical behavior to avoid financial fraud, this ethical behavior is important since the accountant was still a student. Accountant ethics have become a very interesting issue, this issue has developed along with the occurrence of several ethical violations that have occurred both by public accountants, internal accountants and government accountants, therefore ethical rules are important things that must be obeyed. Not a few financial scandals that occur are caused by ethical violations by accountants which ultimately lead to a decline in public trust in the accounting profession. This study aims to determine the effect of locus of control, love of money and emotional intelligence on students' ethical perceptions of the accounting profession. This type of research is quantitative descriptive research. The population of this study was students of the Accounting Study Program, Faculty of Economics and Business, University of 17 August 1945 Semarang, class of 2018 and 2019, totaling 102 students. The sampling technique used saturated or census sampling. Data were collected by distributing questionnaires via Google Form as many as 102 and 80 returned so that the response rate was 78.43 percent. The data analysis technique used was multiple linear regression analysis technique. The results showed that locus of control had a positive and significant effect on students' ethical perceptions of the accounting profession, while love of money and emotional intelligence had a negative and significant effect on students' ethical perceptions of the accounting profession.